Knowledge of the Methods Used by Dentists for Diagnosis and Treatment of Caries Lesions: A Pilot Study - Bárbara Stephanie Leal Dias; Marlus Roberto Rodrigues Cajazeira; Marcia Rejane Thomas Canabarro Andrade (Association of Support to Oral Health Research (APESB), 2024)
Objective: To investigate the methods used by dentists for diagnosis and treatment of dental caries lesions. Material and Methods: This cross-sectional study was developed by sending a validated questionnaire to dentists in the southeastern region of Brazil with questions about detection methods and the indicated procedures for treating lesions. Results: Three hundred and ninety-eight responses were identified after distributing the questionnaire. The state with the highest percentage of respondents was Espírito Santo (n=140). The respondents' mean time since dental school graduation was 12.9 years (±11.4). Regarding the diagnosis, 39.4% of the dentists used the explorer probe to detect occlusal lesions, 79.6% performed drying with an air jet, 65.8% of dentists performed biofilm removal and follow-up for active initial occlusal lesions, and 60.3% applied fluorides. For active caries lesions reaching the enamel dentinal junction, the dentists performed selective caries removal followed by restoration for both occlusal lesions (79.6%) and proximal lesions (78.1%). Conclusion: Visual-tactile and radiographic examinations were the detection methods of most dentists. A conservative approach was identified more frequently for initial, non-cavitated lesions and an operative approach for dentine tissue lesions. Conservative, non-invasive treatment still seems challenging for professionals when lesions reach the dentine tissue.